Worsening of emergency department length of stay during the COVID‐19 pandemic. Issue 3 (22nd June 2021) - Lucero, Anthony; Sokol, Kimberly; Hyun, Jenny; Pan, Luhong; Labha, Joel; Donn, Eric; Kahwaji, Chadi; Miller, Gregg
Abstract: Objective: Our study sought to determine whether there was a change in emergency department (ED) length of stay (LOS) during the coronavirus disease 2019 (COVID‐19) pandemic compared to prior years. Methods: We performed a retrospective analysis using ED performance data 2018–2020 from 56 EDs across the United States. We used a generalized estimating equation (GEE) model to assess differences in ED LOS for admitted (LOS‐A) and discharged (LOS‐D) patients during the COVID‐19 pandemic period compared to prior years. Results: GEE modeling showed that LOS‐A and LOS‐D were significantly higher during the COVID‐19 period compared to the pre‐COVID‐19 period. LOS‐A during the COVID‐19 period was 10.3% higher compared to the pre‐COVID‐19 time period, which represents a higher geometric mean of 28 minutes. LOS‐D during the COVID‐19 period was 2.8% higher compared to the pre‐COVID‐19 time period, which represents a higher geometric mean of 2 minutes. Conclusions: ED LOS‐A and LOS‐D were significantly higher in the COVID‐19 period compared to the pre‐COVID‐19 period despite a lower volume of patients in the COVID‐19 period.